2004
DOI: 10.1083/jcb.200408130
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial barrier disruption by VEGF-mediated Src activity potentiates tumor cell extravasation and metastasis

Abstract: VEGF is unique among angiogenic growth factors because it disrupts endothelial barrier function. Therefore, we considered whether this property of VEGF might contribute to tumor cell extravasation and metastasis. To test this, mice lacking the Src family kinases Src or Yes, which maintain endothelial barrier function in the presence of VEGF, were injected intravenously with VEGF-expressing tumor cells. We found a dramatic reduction in tumor cell extravasation in lungs or livers of mice lacking Src or Yes. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
377
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 438 publications
(395 citation statements)
references
References 16 publications
14
377
1
3
Order By: Relevance
“…Consistent with other findings, in the tumoral context we do not observe any effects on blood vessel density and enlargement upon VEGFC treatment 29,30 or VEGFR3 inhibition 7 . It is worthy of note that these experiments do not It is still unclear whether tumor cell intravasation/extravasation requires the transmigration of cancer cells through the cytoplasm of endothelial cells, as occurs for leukocytes, or whether they transmigrate between two adjacent endothelial cells after the disruption of cell-cell connections 19 . The endothelial barrier integrity is maintained by a complex balance between cell-to-cell adherens junctions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Consistent with other findings, in the tumoral context we do not observe any effects on blood vessel density and enlargement upon VEGFC treatment 29,30 or VEGFR3 inhibition 7 . It is worthy of note that these experiments do not It is still unclear whether tumor cell intravasation/extravasation requires the transmigration of cancer cells through the cytoplasm of endothelial cells, as occurs for leukocytes, or whether they transmigrate between two adjacent endothelial cells after the disruption of cell-cell connections 19 . The endothelial barrier integrity is maintained by a complex balance between cell-to-cell adherens junctions.…”
Section: Discussionmentioning
confidence: 97%
“…In this scenario, VEGFA facilitates cancer cell intravasation by disrupting the VE-Cad-β-catenin complex and inducing adherens junction weakness and formation of transcellular holes 34 . Weis et al, provided evidence that VEGFA-mediated breakdown in blood endothelial integrity through VE-Cad disruption hastens metastases 19 . Moreover, they demonstrated that VE-Cad inhibition compromises endothelial barrier function and promotes tumor cell extravasation 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Même si des progrès ont été réalisés dans la compréhension de la signalisation intracellulaire par laquelle le VEGF promeut la croissance, la survie et la migration endothéliale, comment le VEGF contrôle l'étanchéité vasculaire reste encore mal connu, plus de 20 ans après sa découverte [2]. Des étu-des in vivo et in vitro avaient montré l'implication des tyrosine kinases de la famille Src dans l'augmentation de la perméabilité vasculaire par le VEGF, via la régulation des jonctions intercellulaires [4][5][6]. Parallèlement, l'ablation génétique de la VE-cadhérine ou l'inhibition de sa fonction adhésive augmente la perméabilité…”
Section: La Ve-cadhérine Prend Des Chemins De Traverseunclassified